The intelligibility of Philippine English to selected ASEAN countries - De Leon, Kristine D. (Animo Repository, 2016)
As English gained extensive users, various Englishes started to emerge, and because of this, the question on the intelligibility of these Englishes to other speakers of English arise. From this perspective, the study demonstrates on how intelligible Philippine English is to selected ASEAN countries, especially that ASEAN integration is finally implemented. The study employed three different speakers, acrolectal, mesolectal and basilectal, of Philippine English. These speakers took a couple of tests to confirm that they really belong to the lectal category assigned to them. Aside from the speakers, this study had various listeners, and series of tests were conducted to them, which were from seven members out of ten countries of ASEAN. The results of the study revealed that Philippine English is almost 90% intelligible to the Filipinos due to the familiarity of the variety and probably similarity of the speakers’ first language, and around 65% intelligible to Malaysians. One reason is that English is a second language to Malaysians. For the rest of the ASEAN member countries included in this study, namely Vietnam, Indonesia, Laos, Thailand and Cambodia, the intelligibility rate of Philippine English is less than 50%. The factors that have strongly affected this intelligibility rate are listeners’ familiarity of the variety and the speakers’ effort, choice of words, rate and pronunciation. It also has to be noted that English in these countries is a foreign language, but then the listeners’ perceived language proficiency did not significantly affect the intelligibility of Philippine English. Moreover, their perception of Philippine English did not affect their understanding of the utterances of speakers. Hence, this xv study suggests that interlocutors have to use various strategies in communicating for the utterances to be highly intelligible. When it comes to the different types of speakers of Philippine English, it was found that the mesolectal speaker of Philippine English is more intelligible compared to the acrolectal speaker, whose English is close to General American English, and to the basilectal speaker, whose first language strongly influenced in his speech. Therefore, this indicates that for Filipino English speakers to be understood by different types of listeners in Southeast Asia, the speaker has to adjust his/her speech leaning towards mesolectal speakers’ speech. However, this does not apply to all situations, for the speaker has to be aware to the listeners’ language background, for some listeners, especially American listeners may find acrolectal speech more intelligible. Thus, situational speech intelligibility has emerged from this study, for this caters to how tolerable the speech is to the listeners.